ECAD functionality suitable for web-based optimised automated product variant generation. Issue 1 (11th July 2007) - Schaefer, Dirk; Baguley, Paul
Product variant generation is fundamentally different in Electrical Computer-Aided Design (ECAD) rather than Mechanical Computer-Aided Design (MCAD). The difference lies in the logical relationships between ECAD components. It is not straightforward to select a previous product design to aid product variant generation. Therefore, a new methodology suitable for web-based delivery to support ECAD product variant design is described. Part of the methodology proposed is based on fuzzy logic to select previous ECAD designs from a database of case bases. An additional cost engineering module is proposed to provide the functionality of cost optimisation of the subset of the designs fulfilling a predefined criteria list. The other parts of the methodology have been fully implemented to allow automatic generation of designs in software.